THE SPEECH FUNCTIONS IN THE CONVERSATIONS BETWEEN THE FOURTH SEMESTER ENGLISH DEPARTMENT STUDENTS OF MURIA KUDUS UNIVERSITY AND SOME FOREIGNERS (English Education Journal, 2011)
The fourth semester students of the English department of Muria Kudus University are suggested to take Academic Field Trip in order to provide the studentssome experiences outside of their campus. By observing the English Departmentstudents' interactions with English speakers from other countries, I expect that I can gainclear illustrations on their abilities in maintaining good conversation by applyingappropriate speech functions in the conversation. The main purposes of the study aredescribing the speech functions chosen by the students and the foreigners, explaining therole relation enactment among them, and also describing the contribution of speechfunctions in language education. The data of this study are transcriptions of the studentsand the foreigner's oral communication. I classify the speech functions produced by theparticipants into the speech functions classes introduced by Eggins and Slade. The resultsof the study over the four conversations show that the opening speech functions areproduced mostly by the students; it indicates that the students play as the initiators. Theforeigners show their respect and appreciation to the students as they respond to thestudent initiations by producing more responding and continuing moves. The number ofturns and moves produced by the students and foreigners are quite similar; it indicatesthat both of the participants get the same chance to take their roles. The foreigners astourists show they interest to some tourism objects by describing to the students someobjects they have visited and by comparing to their own country. Learning languagecannot be separated from its culture, therefore speech functions and culturalunderstanding should be taught in the classroom as part of language discourse.